Effect of Dosage and Timing of Coconut Water on Growth and Yield of Tomato Plants (Lycopersicum Esculentum, Mill.) - Juli Santoso Pikir; Ersa Putri Sanjaya; Ramdan Hidayat (Future Science, 2021)
Tomato (Lycopersicum esculentum, mill.) is one of the horticultural commodities with high economic value. The demand is increasing from time to time. One of the factors that decrease productivity in tomato cultivation is due to high flower loss. This study aims to determine the effect of the best dose and time application of coconut water on the growth and yield of tomato plants. The research was conducted in March-June 2020 at the Experimental Garden of the Faculty of Agriculture, UPN “Veteran” Jawa Timur. The research used Completely Randomized Design (CRD) two factors which is dose and time application of coconut water that repeated three times for each treatment combination. The first factor was the dosage of coconut water with 4 levels, 0 ml/p; 500 ml/p; 1000 ml/p, and 1500 ml/p. The second factor was the time application of coconut water with 3 levels, 30 DAP, 45 DAP, and 60 DAP. The results showed that the combination treatment with a dosage of 500 ml with a time of application of 45 DAP showed the highest yields on the total number of harvested fruit, total harvested fruit weight, and fruitset.